The Impact of Membership, Loan, with Transactions on a Rest of The Industry Results (SHU) Cooperative - Chicha Camelia Fizwana; Nesti Hapsari; Nanu Hasanuh (Jurnal Mantik, 2021)
This study aims to determine the effect of the number of loan and savings members on the remaining operating results in the Pindo Deli Karawang employee cooperative in 2008 - 2017. The methodsused in thissresearch is the descriptive verification methodswith a quantitativesapproach. This study uses data from the Pindo Deli Karawang Employee Cooperative for the period 2008 - 2017. This research is a time series type. The data obtained will be analyzed usingsmultiple linearsregression analysis through a partialstests(t-test), simultaneousstest (f test), and coefficientsof determinations(R² test) withsthe helpsof SPSS 22 software. Then, thissstudysusessasnon-probabilityssamplingstechniqueswithsa purposive sampling technique. for taking a sample. The research being tested is the number of members, loans and savings as independent variables and the remaining operating income (SHU) as the dependent variable. This research concentrates on financial accounting which is oriented towards financialestatements. Then, the populationsof this study, namely the Pindo Deli Karawang Employee Cooperative, and the sample of this study were financial statements for 10 years, namely from 2008 – 2017. The results of the study partially show that the number of members, loans, and savings partially have no effect on the remaining operating results of the Pindo Deli Karawang employee cooperative, but simultaneously the number of members, loans, and savings affect the remaining operating results, the value fcount > ftable ie 2,973 > 4.74. The significance value is 0.119 < 0.05. Meanwhile, the coefficient of determination is 59.8%. This shows that the variable Number of Members, Loans, and Savings can affect the Remaining Profits of Cooperatives by 59.8% and the restsis influenced by othersvariables notsincludedsin the study.